If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(5 + -8b) = -5(1 + -4b) (5 * -5 + -8b * -5) = -5(1 + -4b) (-25 + 40b) = -5(1 + -4b) -25 + 40b = (1 * -5 + -4b * -5) -25 + 40b = (-5 + 20b) Solving -25 + 40b = -5 + 20b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-20b' to each side of the equation. -25 + 40b + -20b = -5 + 20b + -20b Combine like terms: 40b + -20b = 20b -25 + 20b = -5 + 20b + -20b Combine like terms: 20b + -20b = 0 -25 + 20b = -5 + 0 -25 + 20b = -5 Add '25' to each side of the equation. -25 + 25 + 20b = -5 + 25 Combine like terms: -25 + 25 = 0 0 + 20b = -5 + 25 20b = -5 + 25 Combine like terms: -5 + 25 = 20 20b = 20 Divide each side by '20'. b = 1 Simplifying b = 1
| m^2-6m-27=0 | | -2y-8=3y+2 | | x^6-124x^3-125=0 | | -7(x-3)=-6(x-5) | | x^6-124x^3=125 | | y+6=-10 | | 3.7b-7=8.1b-19.4 | | -6(-6x-4)=8(-5x-8) | | (2x-1)(x+3)=30 | | 4m^2+9+5m=5m+m^2 | | -3x=-8 | | -5(n-8)-2(6-n)=7-8n+n+1 | | 4+7x=x+5 | | 4x^3+16x^2-48x=0 | | h+p=3(k-8)k | | -6(-6x-4)=8(5x+8) | | 2+.33=1+.25t | | x+(x+2)=-25 | | x+3(3+x)=25 | | 0.75x+.05(12-x)=.10(-106) | | -3(1-3p)-3p=-3(p+1) | | 3(x-3)-6=-7(x+5) | | x+(x+2)=7 | | 0.4x+1.5=2.2-1.5x | | -282=6n | | 8z=(2z+1) | | -8x-6(x-4)=2(x-4) | | 3(w+12)=0 | | 2+2m-2m=-1 | | 4x=10-5x | | t=54-3t | | 0.50x-3=1.5x+4 |